The wounded minister : healing from and preventing personal attacks - Greenfield, Guy. (Grand Rapids, Mich. : Baker Books, 2001)
A compassionate, proactive look at pastoral abuse, a tragic reality that you can do something about. Every church deals with personality conflicts and intermittent discord. But in some congregations, there are people who intentionally attack leaders and initiate a devastating form of abuse: pastoral abuse. A growing phenomenon that cuts across denominational lines and impacts every level of ministry, pastoral abuse leaves in its wake wounded people with ruined ministries, broken relationships, damaged health, even shattered faith. The Wounded Minister examines the reality of evil in churches and the ways in which "clergy killers" or "pathological antagonists" emotionally and spiritually batter pastors. A deft mix of personal experience and in-depth research, this resource will help wounded people of all ministerial positions learn how to recover their broken hearts while rebuilding their lives. As preventive medicine, it also provides guidelines on how sensitive Christians can develop a church structure that protects their pastors from this tragedy.
pt. 1: The reality of abuse. -- Clergy killers on the loose -- Pathological antagonists in the church -- When evil invades the church -- The minister's greatest enemy: passive lay leaders -- The dangers of autonomous church polity -- Wrecking a minister's life and career -- Collateral damage to ministers -- Collateral damage to the church -- pt. 2: Pathological ministers. -- Ministers who invite attack -- Abuse from pathological ministers -- pt. 3: Recovery and healing. -- A ministers' advisory council -- Steps toward healing for abused clergy -- Recovering from shattered dreams -- Wounded healers -- Afterword: growing through rejection.
Includes bibliographical references (pages 227-236).
Keywords: Clergy -- Abuse of; Clergy -- Psychology; Church controversies